Digital Tools in Urban Schools: Mediating a Remix of Learning - Jabari Mahiri (University of Michigan Press, 2011)
Digital Tools in Urban Schools demonstrates significant ways in which high school teachers in the complex educational setting of an urban public high school in northern California extended their own professional learning to revitalize learning in their classrooms. Through a novel research collaboration between a university and this public school, these teachers were supported and guided in developing the skills necessary to take greater advantage of new media and new information sources to increase student learning while making connections to their relevant experiences and interests. Jabari Mahiri draws on extensive qualitative data—including blogs, podcasts, and other digital media—to document, describe, and analyze how the learning of both students and teachers was dramatically transformed as they utilized digital media in their classrooms. Digital Tools in Urban Schools will interest instructional leaders and participants in teacher preparation and professional development programs, education and social science researchers and scholars, graduate and undergraduate programs and classes emphasizing literacy and learning, and those focused on urban education issues and conditions.